Directed Volcanic Blast as a Tragedy of October 26Th, 2010 at Merapi Volcano, Central Java - Igan S. Sutawidjaja (Geological Agency, 2013)
DOI: 10.17014/ijog.v8i3.163Merapi is an active strato volcano located in Central Java. This volcano is regarded as the most active and most dangerous volcano in Indonesia. Since the twentieth century, the activities have comprised mainly the effusive growth of viscous lava domes and lava tongues, with occasional gravitational collapses of parts of over-steepened domes producing pyroclastic flows, commonly defined as “Merapi-Type”. Since October 2010, however, explosive eruptions of a relatively large size have occurred to VEI 4, and some associated pyroclastic flows were larger and had farther reach than any produced on July 2006. These events may also be regarded as another type of eruptions for Merapi. On October26th, 2010 such event happened, even though it was not caused by pyroclastic flows of the dome collapses, about thirty people were killed including Mbah Marijan, known as the Merapi volcano's spiritual gatekeeper, who was found dead at his home approximately 4 km from the crater. The Yogyakarta Palace subsequently confirmed his death. This time the disaster was caused by a sudden directed blast that took place at 17:02 pm throughout Cangkringan, Kinahrejo Village, at the south flank of Merapi Volcano. The victims were the local people who did not predict the blast threatened their areas, because they believed that the pyroclastic flows from the dome collapses as long as they knew, did not threaten their areas, and pyroclastic flows would flow down following the Boyong River as the closest valley to their village. The blast swept an area about 8 km2, reaching about 5 km in distance, deposited thin ash, and toppled all trees to the south around the Kinahrejo and Pakem areas. The blast that reached Kinahrejo Village seemed to have moderate temperatures, because all trees facing the crater were not burnt. However, the victims were affected by dehydration and blanketed by fine ash.